A critical review of recent advances in the diagnosis, classification, and management of uterine adenomyosis. Issue 4 (August 2019) - Tan, Justin; Yong, Paul; Bedaiwy, Mohamed A.
Abstract : Purpose of review: The purpose of this review is to summarize and highlight recent critical advances in the diagnosis, classification, and management of adenomyosis. Recent findings: Recent studies have clarified the specific mechanism through which adenomyotic lesions invade the underlying myometrium by epithelial–mesenchymal transition. Correlation studies using diagnostic MRI also strongly support the hypothesis of a different pathogenesis between the inner and outer myometrium forms of adenomyosis. Given advances in diagnostic imaging, several international organizations have also highlighted the importance of classification systems for adenomyosis. Finally, selective progesterone receptor modulators and gonadotropin-releasing hormone antagonists have demonstrated significant promise for treating pelvic pain and bleeding associated with adenomyosis, whereas novel fertility-preserving surgical techniques have been introduced to excise diffuse adenomyotic pathology while maintaining adequate uterine integrity. Summary: Recent attempts at a uniform and reproducible classification system likely represent the first step for the development of a staging system for adenomyosis that can be correlated with the severity of clinical symptoms and promote an individualized therapeutic approach. Simultaneously, further insights into the etiology and pathogenesis as outlined in this review may also help in the development of targeted medical therapies.